Synthesis and Spectral Analysis of Chromium, Copper Complexes of 2-Hydroxy-1, 2-diphenylethan-1 - Mir, Mohd Amin; Hasnain, Syed M.; Dernayka, Samar (Physics and Chemistry of Solid State, 2024)
Various chemical process have been utilized to analyze chromium (II) and copper (II) complexes with Benzoin. The fore mentioned complexes were analyzed for elemental analyses, and characterized by infrared, electronic spectra, NMR spectroscopy. The data analysis showed the metal ion formation of 1:1 ligand to metal ratio representing the [Cr (B)] H2O and [Cu (B)] 2H2O ionic complex in which B represents the Benzoin. According to the data analyzed by Infrared spectroscopy, it is through the carbonyl and hydroxyl oxygen’s of the Benzoin that chelation chemistry takes place. The complex structural analysis was elucidated by electronic spectral data analysis and by proton NMR spectroscopy. The complex systems with the metals also showed antimicrobial property against many bacterial strains.